28.7k views
5 votes
Solve the equation by factoring 6x^2-17x+13=20x^2-32

2 Answers

1 vote

6x^2 - 17x+13 = 20x^2 - 32

14x^2 + 17x - 45 = 0

(2x + 5)(7x - 9) = 0

2x + 5 = 0

2x = -5

x = -5/2

7x - 9 = 0

7x = 9

x = 9/7

Answer

x = -5/2 , 9/7

User Tobias Ribizel
by
4.7k points
3 votes

Answer:


x=(-5)/(2)


x=(9)/(7)

Explanation:


6x^2-17x+13=20x^2-32

combine like terms and simplify the equation

Subtract 6x^2 from both sides


6x^2-17x+13=20x^2-32


-17x+13=14x^2-32

Add 17x on both sides


13=14x^2+17x-32

Now subtract 13 from both sides


0=14x^2+17x-45

Now we solve for x

Apply quadratic formula : a= 14, b= +17 and c= -45


x=(-b+-√(b^2-4ac) )/(2a)


x=(-17+-√(17^2-4(14)(-45)) )/(2(14))


x=(-17+-53)/(28)

Now make two equations


x=(-17+53)/(28)=(-5)/(2)


x=(-17-53)/(28)=(9)/(7)

User Kacper Polak
by
5.3k points